Structural, mechanical, and optoelectronic properties of siladiamanes – Novel hypothetical silicon analogs of diamanes: A combined DFT and DFTB study - R. Kevorkyants (Next Materials)
This work describes structural, mechanical, and optoelectronic properties of the AA- and AB-stacked siladiamanes. Siladiamanes are hypothetical silicon analogues of diamanes – semiconducting quasi 2D diamonds. According to DFT calculations, the AA- and AB-stacked siladiamanes are thermodynamically, dynamically, and mechanically stable. Molecular dynamics simulations within DFTB theoretical framework demonstrate their stability at atmospheric pressure and at temperatures well above 400 K. The AA- and AB-stacked siladiamanes are indirect bandgap semiconductors with HSE06 electronic bandgaps equal to 1.88 eV and 2.10 eV, respectively. Notably, energies of direct electronic transitions in both materials are practically the same as those of the indirect ones. Mechanical properties of the siladiamanes are comparable to those of the corresponding diamanes and some well-known 2D and quasi 2D compounds. In addition to prospective (electro)photocatalytic, photovoltaic, and optical applications, siladiamanes pave the way to an ultimate miniaturization of conventional computer chips.